Sublethal tree health conditions suppress tree growth across eastern US forests - K. Diego Rocha; Lukas J. Magee; Denver T. Cayetano; D. Alex Bowers; Kristina J. Anderson-Teixeira; Sean M. McMahon; Jessica Shue; David A. Orwig; Stephanie Bohlman; Jason Vogel; Timothy A. Martin; William J. McShea; et al. (Forest Ecology and Management, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

No sex differences in fat oxidation in response to exercise prescribed according to maximal heart rate or ventilatory threshold - Todd A. Astorino; Alex J. MacDonald; Alex Anderson; Hanna Lauritzen; Ryan Pinter; Hailey Schepper; Dalton Ferguson (European Journal of Applied Physiology, 2026)

Spatiotemporal dynamics of burned areas in the Caatinga Biome, Brazil: a GIS-based assessment - Suelem Farias Soares Martins; Alex Mota dos Santos; Carlos Fabricio Assunção da Silva; Fabrizia Gioppo Nunes; Alexandre Arnhold; Anderson Paulo Rudke; Gerson dos Santos Lisboa (Applied Geomatics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effectiveness of Moringa oleifera, chitosan, and alum as adsorbents in lake water treatment - Yvan Anderson Tchangoue Ngandjui; Paul Atabong Agendia; Alex Tawanda Kuvarega; Volodymyr Tarabara; Titus Alfred Makudali Msagati (Environmental Science and Pollution Research, 2026)
This study evaluated the effects of Moringa oleifera (MO), chitosan, and alum as adsorbents on the physicochemical properties of water collected from Lake Florida in Johannesburg, South Africa. The lake water was subjected to three different treatments using jar tests at concentration dosages of 25, 30, and 35 mL and settling times of 30, 60, and 90 min. The water treated with adsorbents significantly reduced turbidity ( p < 0.05) with removal efficiencies of 99.33% for MO (30 mL, 30 min), 99.22% for chitosan (35 mL, 60 min), and 99.60% for alum (25 mL, 60 min). Dissolved oxygen increased significantly (p < 0.05) from 2.06 ± 0.02 mg/L to 3.24 ± 0.01 mg/L with chitosan (25 mL, 90 min) and MO (35 mL, 90 min), and to 3.15 ± 0.01 mg/L with alum (25 mL, 60 min). Sulfate levels increased with MO from 65.00 ± 1.00 mg/L to 200.67 ± 0.58 mg/L (35 mL, 90 min) , while alum caused an initial decrease to 49.67 ± 0.58 mg/L (25 mL, 30 min), followed by an increase to 71.33 ± 0.58 mg/L. Furthermore, total dissolved solids and conductivity increased with MO, whereas chitosan and alum caused no significant changes. However, a slight pH reduction was noted, with no significant nitrate alteration. Based on principal component analysis, the key factors driving water quality variations in the dataset were treatment type and retention time, with parameters such as pH, conductivity, and sulfate being strong indicators of treatment efficiency. Dissolved oxygen and nitrate were more dependent on treatment time. These findings provide insights into the performance of different adsorbents and their impacts on lake water quality. Graphical Abstract

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Explorative Evaluation of the Adsorptive Potential of Quercus robur and Quercus rugosa for Lake Water Treatment - Yvan Anderson Tchangoue Ngandjui; Titus Alfred Makudali Msagati; Alex Tawanda Kuvarega (Water, Air, & Soil Pollution, 2025)
This study assessed and compared the effects of Quercus robur (QRO) and Quercus rugosa (QRU) seed extracts as natural coagulants on the physicochemical properties of lake water in Johannesburg. Jar test experiments were conducted using dosage concentrations of 15, 20, and 25 mL, with settling times of 30, 60, and 90 min. The treatments led to 100% turbidity removal across all tested dosages within 90 min. Dissolved oxygen significantly improved, increasing from 1.65 ± 0.02 mg/L in raw lake water to 2.39 ± 0.01 mg/L and 2.33 ± 0.01 mg/L after treatments with QRU and QRO, respectively. Conversely, pH levels decreased from 7.42 ± 0.03 to 7.06 ± 0.02 with QRO and 7.16 ± 0.04 with QRU. Total dissolved solids were reduced from 97.67 ± 1.53 mg/L to 70.33 ± 0.58 mg/L with QRO and 71.33 ± 0.58 mg/L using QRU. A corresponding decline in conductivity was observed, from 192.0 ± 1.0 µS/cm to 141.33 ± 0.58 µS/cm with QRO and 142.33 ± 0.58 µS/cm with QRU. Principal Component Analysis (PCA) highlighted clear distinctions between treated samples and raw lake water, with the treated samples clustering away from untreated water and aligning with improved physicochemical indicators. The findings demonstrate the efficacy of Q. robur and Q. rugosa seed extracts in enhancing water quality and their suitability as low-cost, natural alternatives to conventional coagulants. Post-treatment values for all key parameters met the World Health Organization's recommended limits for drinking water, underscoring the potential of these materials for sustainable water purification.

Telmisartan mitigates behavioral and cytokine level alterations but impairs spatial working memory in a phencyclidine-induced mouse model of schizophrenia - Ana Carolina Dutra-Tavares; Julyana Gomes Maia; Thainá Pereira de Souza; Claudio Carneiro Filgueiras; Anderson Ribeiro-Carvalho; Alex Christian Manhães; Yael Abreu-Villaça (Psychopharmacology, 2025)

Gas exchange and antioxidant metabolism of Cedrela fissilis Vell. seedlings under varying water and light availability - Juliana Milene Silverio; Silvana de Paula Quintão Scalon; Cleberton Correia Santos; Anderson dos Santos Dias; Diego Pereira; Rian Alex Lopes Janse; João Paulo de Castro Souza; Luis Guilherme Rodrigues Macedo (Flora, 2025)

Insights from remote sensing for the study of deforestation drivers in savannas - Carlos Fabricio Assunção da Silva; Alex Mota dos Santos; Anderson Paulo Rudke; Fabrizia Gioppo Nunes; Swanni T Alvarado (Journal for Nature Conservation, 2025)

Migratory patterns and seasonal habitat use of great hammerhead sharks ( Sphyrna mokarran ) in the southeastern United States - Grace A. Casselberry; Gregory B. Skomal; Lucas P. Griffin; Jacob W. Brownscombe; John T. Finn; Joseph Dello Russo; Alex Filous; Peter E. Holder; Ben Daughtry; Jeff Kneebone; Danielle Morley; Susan K. Lowerre‐Barbieri; et al. (Journal of Fish Biology, 2025)
The great hammerhead shark ( Sphyrna mokarran ) is a highly mobile shark species whose population in the United States declined dramatically through the early 2000s. Their spatial ecology is poorly understood, creating challenges for effective conservation of this enigmatic marine predator. Using acoustic telemetry and network analyses, we describe the movement patterns of 15 mature great hammerhead sharks (207–331.5 cm fork length) primarily within the waters of the southeastern United States from April 2019 to December 2022, including identifying movement corridors, core use areas and seasonal shifts in habitat use. Great hammerheads exhibited partial migration; some sharks undertook consistent, repeatable, round‐trip migrations between the tagging site in the Florida Keys and northern points in the Gulf of Mexico and Atlantic coast. Conversely, others remained in the Florida Keys year‐round. Network analysis coupled with community detection algorithms revealed that individual great hammerheads displayed oceanic basin affinity, favouring migration to either the Atlantic Ocean or Gulf of Mexico. Great hammerheads that remained in the Florida Keys shifted their habitat use seasonally from inshore channels (spring and summer) to offshore artificial reefs and the natural reef tract (summer through winter). These shifts may be driven by prey availability, as core use areas often corresponded to known locations of seasonal spawning aggregations for reef fish. These data fill an important knowledge gap for great hammerhead migratory patterns that can improve spatial management strategies for this historically overexploited species. We discuss the importance of drawing upon data from multiple tagging locations for highly mobile species management, particularly in the designation of essential fish habitat.

Generalized Cerebellar Ataxia of Acute Onset: Case Report - Arthur Antônio Freire Alves; Arthur Felipe Barbosa Vasconcelos; Francisco Anderson de Sá Carvalho; Gilmar Leite Pessoa Filho; Ana Luísa Castelo Branco Gomes; Adriana M. T. Nepomuceno; Juliana Magalhães Leite; Rafael de Souza Andrade; João Alfredo M. M. Barros; Alex Tiburtino Meira (The Cerebellum, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Triangulating habitat suitability for the locally extirpated California grizzly bear - Alex McInturff; Peter S. Alagona; Scott D. Cooper; Kaitlyn M. Gaynor; Sarah E. Anderson; Elizabeth S. Forbes; Robert Heilmayr; Elizabeth H.T. Hiroyasu; Bruce E. Kendall; Alexis M. Mychajliw; Molly Hardesty-Moore (Biological Conservation, 2025)

Effects and economic viability of earthworm meal (Eisenia andrei) and zeolite in diets for Nile tilapia (Oreochromis niloticus) fingerlings - Alex Steven Valencia Ortiz; Guilherme Melgaço Heluy; Maria do Carmo Mohaupt Marques Ludke; Luis Otávio Brito; Juliana Ferreira dos Santos; Carlos Bôa-Viagem Rabello; Jorge Vitor Ludke; Adrielle Carneiro de Araújo Santos; Elton Francisco de Oliveira; José Anderson Gomes da Silva; Arlei Coldebella (Aquaculture International, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Urban greenery distribution and its link to social vulnerability - Yingjie Liu; Xinyue Gu; Zeyu Wang; Alex Anderson (Urban Forestry & Urban Greening, 2024)

The drivers of fire in the Caatinga Biome in Brazil - Suelem Farias Soares Martins; Alex Mota dos Santos; Carlos Fabricio Assunção da Silva; Anderson Paulo Rudke; Swanni T. Alvarado; José Lucas da Silva Melo (Forest Ecology and Management, 2024)

Effect of hyaluronic acid-stabilized silver nanoparticles on lettuce (Lactuca sativa L.) seed germination - Débora R. Antunes; Mariana M.L.H. Forini; Yasmin A. Coqueiro; Montcharles S. Pontes; Pedro H.C. Lima; Luiz A.F. Cavalcante; Alex O. Sanches; Anderson R.L. Caires; Etenaldo F. Santiago; Renato Grillo (Chemosphere, 2024)

Image-based volume estimation for food in a bowl - Wenyan Jia; Boyang Li; Qi Xu; Guangzong Chen; Zhi-Hong Mao; Megan A. McCrory; Tom Baranowski; Lora E. Burke; Benny Lo; Alex K. Anderson; Gary Frost; Edward Sazonov; et al. (Journal of Food Engineering, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Sampling completeness changes perceptions of continental scale climate–species richness relationships in odonates - Fernanda Alves‐Martins; Juliana Stropp; Leandro Juen; Richard J. Ladle; Jorge M. Lobo; Javier Martinez‐Arribas; Paulo De Marco Júnior; Leandro Schlemmer Brasil; Victor Rennan Santos Ferreira; Rafael Costa Bastos; Alex Córdoba‐Aguilar; Emmy Fiorella Medina‐Espinoza; et al. (Journal of Biogeography, 2024)
Aim Insects are one of the least studied taxa, with most species lacking basic ecological and biogeographical information. This problem is particularly acute in the tropics, where low sampling effort hampers accurate estimates of species richness at scale and potentially confounds efforts to identify the drivers of biogeographical gradients. Here, we evaluate the quality of the data on the distribution and diversity of odonate species in the Neotropics, while also examining the influence of sampling completeness on climate–richness relationships using a comprehensive database of odonates. Location The Neotropics. Taxon Odonata. Methods Using 56,535 records collected from 1970 to 2021, we assess whether climate–species richness models vary under different scenarios of survey completeness. Results Our survey compilation revealed that most Neotropical diversity of Odonata likely remains unknown. Only 1% of the one‐degree cells covering the Neotropics held reliable information on odonate species richness, with particularly severe gaps in the Caribbean, Central America, northeastern Brazil and northern Chile. Temperature, precipitation and potential evapotranspiration exert consistent effects on Odonata richness across the entire Neotropics, regardless the level of survey completeness. Whereas seasonality‐related variables are less important predictors of species richness at the biogeographical scale. Main Conclusions By highlighting areas where inventories are more reliable and identifying regions that require increased data collection efforts and mobilization, our assessment offers a roadmap for improving the reliability of odonate inventories in the Neotropics. Furthermore, our findings underscore the importance of accounting for varying levels of survey completeness in macroecological models to reveal robust climate–species richness relationships. Simultaneously, they highlight strong climatic predictors of species richness, irrespective of survey effort intensity. These predictors provide a solid foundation for modelling and predicting odonate species richness in the Neotropics.

Relative Sowing Time and Spatial Arrangement in Upland Rice/Legume Intercropping Systems - Flávia Constantino Meirelles; Adailza Guilherme Cavalcante; Alex Rangel Gonzaga; Anderson Prates Coelho; Wopke van der Werf; Lammert Bastiaans; Orivaldo Arf; Leandro Borges Lemos (International Journal of Plant Production, 2024)

Examination of the correlation between SPT and undrained shear strength: Case study of clay till in Alberta, Canada - Chao Kang; Mark Brotherton; Karen Anderson; Kevin Semeniuk; Gavin Mayer; Alex Law; Zhenyao Xia; Lun Zhang; Ali Farrag; Jin You; Majed Abdallah (Engineering Geology, 2024)

BjussuMP-II, a venom metalloproteinase, induces the release and cleavage of pro-inflammatory cytokines and disrupts human umbilical vein endothelial cells - Hallison Mota Santana; Yoda Janaina Ikenohuchi; Milena Daniela Souza Silva; Braz Junior Campos Farias; Suzanne Nery Serrath; Carolina Pereira Da Silva; João Gabriel dos Santos Magalhães; Larissa Faustina Cruz; Daniel Gomes Cardozo; Alex Ferreira e Ferreira; Valdison Pereira Dos Reis; Rafaela Diniz-Sousa; et al. (Chemico-Biological Interactions, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Evaluation and comparison of MODIS aerosol optical depth retrieval algorithms over Brazil - Anderson Paulo Rudke; Jorge Alberto Martins; Leila Droprinchinski Martins; Carolina Letícia Zilli Vieira; Longxiang Li; Carlos Fabricio Assunção da Silva; Alex Mota dos Santos; Petros Koutrakis; Taciana Toledo de Almeida Albuquerque (Atmospheric Environment, 2023)

Parenting Practices Are Associated With Adolescent Food Choices During Independent Eating Occasions - Marla Reicks; Karina R. Lora; Yichen Jin; Alex K. Anderson; Lillie Monroe-Lord; Blake L. Jones; Glade L. Topham; Jinan Banna; Carolyn Gunther; Laura C. Hopkins; Rickelle Richards; Siew Sun Wong (Journal of the Academy of Nutrition and Dietetics, 2023)

Neonatal phencyclidine as a model of sex-biased schizophrenia symptomatology in adolescent mice - Ana Carolina Dutra-Tavares; Thainá P. Souza; Juliana O. Silva; Keila A. Semeão; Felipe F. Mello; Claudio C. Filgueiras; Anderson Ribeiro-Carvalho; Alex C. Manhães; Yael Abreu-Villaça (Psychopharmacology, 2023)

Adolescent Independent Eating Occasions, Dietary Intake, and Parenting Practices During the COVID-19 Pandemic: A Qualitative Study of Parents and Adolescents From Households With Low Income - Carolyn Gunther; Jinan Banna; Blake L. Jones; Catherine Park; Marla Reicks; Rickelle Richards; Heather Schier; Glade L. Topham; Siew Sun Wong; Alex K. Anderson; Miriam Ballejos; Laura C. Hopkins; et al. (Journal of Nutrition Education and Behavior, 2023)

Spinsim: A GPU optimized python package for simulating spin-half and spin-one quantum systems - Alex Tritt; Joshua Morris; Joel Hochstetter; R.P. Anderson; James Saunderson; L.D. Turner (Computer Physics Communications, 2023)

Macroecological and biogeographical patterns of limb reduction in the world's skinks - Marco Camaiti; Alistair R. Evans; Christy A. Hipsley; Mark N. Hutchinson; Shai Meiri; Rodolfo de Oliveira Anderson; Alex Slavenko; David G. Chapple (Journal of Biogeography, 2023)
Aim Limb reduction is a dramatic evolutionary transition, yet whether it is achieved in similar trajectories across clades, and its environmental drivers, remain unclear. We investigate the macroevolutionary and biogeographical patterns of limb reduction in skinks, where limb reduction occurred more often than in any other tetrapod clade, and test their associations with substrate categories using a global database. We test for habitat associations of body shapes in a group of Australian skinks using quantitative habitat data. Location Global (Scincidae), Australia (Sphenomorphinae). Taxon Skinks, Australian Sphenomorphinae. Materials and Methods We use morphological data to explore the patterns of limb reduction in the world's skinks, investigating how body proportions differ across skink clades and subfamilies. We examine the relationships between body shape and substrate (coarsely classified). Further, we investigate the relationships between body shape and high‐resolution soil and climate properties extracted from each species' distribution for Australian sphenomorphines. Results Relationships between limb lengths and trunk elongation show idiosyncratic patterns across skink clades. Presacral vertebrae numbers positively correlate with trunk elongation in all taxa, except Glaphyromorphus . Skinks from sandy habitats show greater disparity between forelimb and hindlimb lengths than all other substrate categories. In sphenomorphines, shorter limbs and elongated trunks correlate with colder, more humid microhabitats and richer soils; high limb disparity correlates with hot, arid microhabitats and sandy, poor substrates. Main Conclusions The evolutionary trajectories of limb reduction in skinks are clade‐specific and sometimes unique. Selection for specific limb proportions and body sizes in limb‐reduced forms changes across substrates. On poor, sandy substrates of arid environments, body shapes with longer hindlimbs may be more efficient for locomotion in a granular fluid (i.e. sand) and exploit the air–substrate interface than complete limblessness. On richer, more humid substrates, such morphology is rare, indicating that navigating cluttered substrates selects for more equal and shorter limb lengths.

The occurrence of antimicrobial residues and antimicrobial resistance genes in urban drinking water and sewage in Southern Brazil - Rafaela Ramalho; Lisiane Cervieri Mezzomo; William Machado; Camila da Silva Morais Hein; Camila Zanfelice Müller; Thaisla Cristiane Borella da Silva; Louise Jank; Alex Elias Lamas; Rogério Antônio da Costa Ballestrin; Priscila Lamb Wink; Anderson Araújo de Lima; Gertrudes Corção; et al. (Brazilian Journal of Microbiology, 2022)

A database of the morphology, ecology and literature of the world's limb‐reduced skinks - Marco Camaiti; Alistair R. Evans; Christy A. Hipsley; Mark N. Hutchinson; Shai Meiri; Rodolfo O. Anderson; Alex Slavenko; David G. Chapple (Journal of Biogeography, 2022)
Aim Limb‐reduced squamates are a convenient model system to investigate macroevolutionary trends in morphology. Here, we provide morphological, ecological and literature data on all known species of limb‐reduced skinks (Scincidae) and their relatives, representing one of the most diverse and widely distributed groups of limb‐reduced squamates. Location Global. Taxon Skinks (Reptilia, Squamata: Scincidae). Limb‐reduced forms. Methods Morphological data were sourced from the primary literature, spanning a period of over 150 years. Linear body measurements were averaged across all values in the literature, preserving proportionality to body length. For digits and presacral vertebrae, we used maximum recorded counts. Ecological and biogeographical data were sourced from habitat assessments in the primary literature, online databases and field guides. Literature data were sorted according to type of study. To exemplify the applicability of the database, we used Markov‐chain ordered models to estimate the evolutionary frequency of limb reduction and loss in skinks. Results We find evidence of limb reduction and loss in a total of 394 species worldwide, representing ~23% of all skink species, and ~30% of genera. The distribution of limb‐reduced and limbless forms differs from that of fully limbed forms, as they are present in all biogeographic realms with the almost complete exclusion of the Americas. We estimate that limb reduction evolved more than 50 times in skinks, and that loss of at least one limb pair evolved at least 24 times. Main conclusions The dataset captures a broad spectrum of morphological and ecological variation in a large, globally distributed taxonomic group. It establishes a widely applicable definition of limb reduction based on limb proportions as a reference for future studies. Such an extensive collection of morphological and ecological data can pave the way for investigations of dramatic morphological transitions and their ecological drivers at a global and local scale.

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

Microbiome and environment explain the absence of correlations between consumers and their diet in Bornean microsnails - Kasper P. Hendriks; Karen Bisschop; Hylke H. Kortenbosch; James C. Kavanagh; Anaïs E. A. Larue; Phung Chee‐Chean; Dries Bonte; Elza J. Duijm; Joana Falcão Salles; Alex L. Pigot; Francisco J. Richter Mendoza; Menno Schilthuizen; et al. (Ecology, 2021)
Classical ecological theory posits that species partition resources such that each species occupies a unique resource niche. In general, the availability of more resources allows more species to co‐occur. Thus, a strong relationship between communities of consumers and their resources is expected. However, correlations may be influenced by other layers in the food web, or by the environment. Here we show, by studying the relationship between communities of consumers (land snails) and individual diets (from seed plants), that there is in fact no direct, or at most a weak but negative, relationship. However, we found that the diversity of the individual microbiome positively correlates with both consumer community diversity and individual diet diversity in three target species. Moreover, these correlations were affected by various environmental variables, such as anthropogenic activity, habitat island size, and a possibly important nutrient source, guano runoff from nearby caves. Our results suggest that the microbiome and the environment explain the absence of correlations between diet and consumer community diversity. Hence, we advocate that microbiome inventories are routinely added to any community dietary analysis, which our study shows can be done with relatively little extra effort. Our approach presents the tools to quickly obtain an overview of the relationships between consumers and their resources. We anticipate our approach to be useful for ecologists and environmentalists studying different communities in a local food web.

Forced swimming stress increases natatory activity of lead-exposed mice - Ulisses C. Araujo; Thomas E. Krahe; Anderson Ribeiro-Carvalho; Regina A. A. Gomes; Bruna M. Lotufo; Maria de Fátima R. Moreira; Yael de Abreu-Villaça; Alex C. Manhães; Cláudio C. Filgueiras (Toxicological Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Framework for assessing vertebrate invasive species damage: the case of feral swine in the United States - Stephanie Shwiff; Alex Pelham; Steven Shwiff; William Haden-Chomphosy; Vienna R. Brown; Karina Ernst; Aaron Anderson (Biological Invasions, 2020)
The aim of this study is to provide a general overview of the economic impacts associated with vertebrate invasive species (VIS) in the United States and suggests a methodology for differentiating types of damage. We identify a general framework for categorizing VIS damage that separates this damage into three main categories: destruction, depredation, and disease. We then examine how this framework fits into current published estimates of damage and management costs. Economic impacts associated with feral swine damage and management are plentiful enough to warrant separate treatment from other VIS and are observed in all three categories. For all VIS examined in this study, damage estimates associated with destruction provide the most evaluations of VIS impacts, especially destruction of crops. Evaluations of the losses associated with depredation are largely absent from the literature. We find that while published studies have estimated substantial economic impact associated with VIS, the current state of the literature focusing on VIS frequently fails to address all of the categories of damage, is difficult to compare or replicate, and is unsuited for extrapolation to nation-wide estimates of damage.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Spatio-temporal distribution of polar cod (Boreogadus saida) and saffron cod (Eleginus gracilis) early life stages in the Pacific Arctic - Cathleen D. Vestfals; Franz J. Mueter; Janet T. Duffy-Anderson; Morgan S. Busby; Alex De Robertis (Polar Biology, 2019)

Evaluation of TSEB turbulent fluxes using different methods for the retrieval of soil and canopy component temperatures from UAV thermal and multispectral imagery - Héctor Nieto; William P. Kustas; Alfonso Torres-Rúa; Joseph G. Alfieri; Feng Gao; Martha C. Anderson; W. Alex White; Lisheng Song; María del Mar Alsina; John H. Prueger; Mac McKee; Manal Elarab; et al. (Irrigation Science, 2019)

Land‐sparing agriculture sustains higher levels of avian functional diversity than land sharing - Patrick G. Cannon; James J. Gilroy; Joseph A. Tobias; Alex Anderson; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2019)
The ecological impacts of meeting rising demands for food production can potentially be mitigated by two competing land‐use strategies: off‐setting natural habitats through intensification of existing farmland (land sparing), or elevating biodiversity within the agricultural matrix via the integration of “wildlife‐friendly” habitat features (land sharing). However, a key unanswered question is whether sparing or sharing farming would best conserve functional diversity, which can promote ecosystem stability and resilience to future land‐use change. Focusing on bird communities in tropical cloud forests of the Colombian Andes, we test the performance of each strategy in conserving functional diversity. We show that multiple components of avian functional diversity in farmland are positively related to the proximity and extent of natural forest. Using landscape and community simulations, we also show that land‐sparing agriculture conserves greater functional diversity and predicts higher abundance of species supplying key ecological functions than land sharing, with sharing becoming progressively inferior with increasing isolation from remnant forest. These results suggest low‐intensity agriculture is likely to conserve little functional diversity unless large blocks of adjacent natural habitat are protected, consistent with land sparing. To ensure the retention of functionally diverse ecosystems, we urgently need to implement mechanisms for increasing farmland productivity whilst protecting spared land.

Earth Observations and Integrative Models in Support of Food and Water Security - Stephanie Schollaert Uz; Alex C. Ruane; Bryan N. Duncan; Compton J. Tucker; George J. Huffman; Iliana E. Mladenova; Batuhan Osmanoglu; Thomas R. H. Holmes; Amy McNally; Christa Peters-Lidard; John D. Bolten; Narendra Das; et al. (Remote Sensing in Earth Systems Sciences, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Coupling the terrestrial hydrology model with biogeochemistry to the integrated LAND surface model: Amazon Basin applications - Aline Anderson de Castro; Luz Adriana Cuartas; Michael T. Coe; Celso Von Randow; Andrea Castanho; Alex Ovando; Antonio Donato Nobre; Adriana Koumrouyan; Gilvan Sampaio; Marcos Heil Costa (Hydrological Sciences Journal, 2018)

Indices of Canada’s future climate for general and agricultural adaptation applications - Guilong Li; Xuebin Zhang; Alex J. Cannon; Trevor Murdock; Steven Sobie; Francis Zwiers; Kevin Anderson; Budong Qian (Climatic Change, 2018)

Inventory on the dietary assessment tools available and needed in africa: a prerequisite for setting up a common methodological research infrastructure for nutritional surveillance, research, and prevention of diet-related non-communicable diseases - Pedro T. Pisa; Edwige Landais; Barrie Margetts; Hester H. Vorster; Christine M. Friedenreich; Inge Huybrechts; Yves Martin-prevel; Francesco Branca; Warren T. K. Lee; Catherine Leclercq; Johann Jerling; Francis Zotor; et al. (Critical Reviews in Food Science and Nutrition, 2018)

Vertical (arboreality) and horizontal (dispersal) movement increase the resilience of vertebrates to climatic instability - Brett. R. Scheffers; Luke Shoo; Ben Phillips; Stewart L. Macdonald; Alex Anderson; Jeremy VanDerWal; Collin Storlie; Arnaud Gourret; Stephen E. Williams (Global Ecology and Biogeography, 2017)
Aim Species that respond favourably to environmental change tend to be mobile or dispersive. Living within trees has some benefits over life on the ground. Species that move vertically within forest canopies can take advantage of increased complexity and resource availability, which should correspond to increased resilience to environmental variability and change. Here we show that two modes of movement, arboreality and horizontal dispersal, across an entire bioregional vertebrate fauna in the rain forests of Australia are associated with measures of historical environmental stability. Location Wet Tropics, Queensland, Australia. Time period Historical (c. 20,000 years ago) and current (1990‐2009). Major taxa studied Mammal, bird, reptile, and frog species. Methods We analysed vertebrate distribution for 195 species and trait data from 20 years of standardized sampling. We derived an arboreality index (i.e., the extent of vertical habitat used by each species) from a large database of field observations combined with expert opinion scores on arboreality. We compared community‐wide trends in arboreality and their horizontal dispersal potential with historical climate since the Last Glacial Maximum ( c . 20,000 years ago) and current climate over 20 years of the recent past (1990–2009). Results Vertical (arboreality) and horizontal (dispersal) movement were positively correlated, and both were negatively correlated with environmental stability. We found that arboreal species dominate communities in historically unstable areas, and these areas have both low richness and low endemism. Further, we show that low‐ and high‐altitude arboreal species experience similar thermal regimes, whereas low‐ and high‐altitude ground‐dwelling species experience little overlap in thermal regimes. Main conclusion Higher variability and overlap in temperature among rain forest canopies suggests less geographical separation in tolerable conditions for arboreal taxa when compared with ground‐dwelling taxa. Increased ecological plasticity in horizontal and vertical movement as well as exposure and pre‐selection to high temperature variability appears to allow arboreal species to exploit climatically uncertain areas, a capacity that may serve them well in responding to future climate change.

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Temperature variability and early clustering of record-breaking events - Amalia Anderson; Alex Kostinski (Theoretical and Applied Climatology, 2016)

Assessing the value of a marine world heritage site to the ecology and conservation of apex predatory sharks - Acuna Marrero David; Hearn Alex; Hammerschlag Neil; Calich Hannah; Anderson Marti; Pawley Matthew; Salinas De Leon Pelayo (Frontiers in Marine Science, 2016)

A metagenetic approach to determine the diversity and distribution of cyst nematodes at the level of the country, the field and the individual - Sebastian Eves‐van den Akker; Catherine J. Lilley; Alex Reid; Jon Pickup; Eric Anderson; Peter J.A. Cock; Mark Blaxter; Peter E. Urwin; John T. Jones; Vivian C. Blok (Molecular Ecology, 2015)
Distinct populations of the potato cyst nematode ( PCN ) Globodera pallida exist in the UK that differ in their ability to overcome various sources of resistance. An efficient method for distinguishing between populations would enable pathogen‐informed cultivar choice in the field. Science and Advice for Scottish Agriculture ( SASA ) annually undertake national DNA diagnostic tests to determine the presence of PCN in potato seed and ware land by extracting DNA from soil floats. These DNA samples provide a unique resource for monitoring the distribution of PCN and further interrogation of the diversity within species. We identify a region of mitochondrial DNA descriptive of three main groups of G. pallida present in the UK and adopt a metagenetic approach to the sequencing and analysis of all SASA samples simultaneously. Using this approach, we describe the distribution of G. pallida mitotypes across Scotland with field‐scale resolution. Most fields contain a single mitotype, one‐fifth contain a mix of mitotypes, and less than 3% contain all three mitotypes. Within mixed fields, we were able to quantify the relative abundance of each mitotype across an order of magnitude. Local areas within mixed fields are dominated by certain mitotypes and indicate towards a complex underlying ‘pathoscape’. Finally, we assess mitotype distribution at the level of the individual cyst and provide evidence of ‘hybrids’. This study provides a method for accurate, quantitative and high‐throughput typing of up to one thousand fields simultaneously, while revealing novel insights into the national genetic variability of an economically important plant parasite.

Wastewater Nitrogen Contributions to Coastal Plain Watersheds, NC, USA - Guy Iverson; Michael A. O’Driscoll; Charles P. Humphrey; Alex K. Manda; Eliot Anderson-Evans (Water, Air, & Soil Pollution, 2015)

Tobacco smoke containing high or low levels of nicotine during adolescence: effects on novelty-seeking and anxiety-like behaviors in mice - Yael Abreu-Villaça; Cláudio C. Filgueiras; Monique Correa-Santos; Cristiane C. Cavina; Victor F. Naiff; Thomas E. Krahe; Alex C. Manhães; Anderson Ribeiro-Carvalho (Psychopharmacology, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Comparison of Phosphorus Concentrations in Coastal Plain Watersheds Served by Onsite Wastewater Treatment Systems and a Municipal Sewer Treatment System - Charles P. Humphrey; Eliot Anderson-Evans; Michael O’Driscoll; Alex Manda; Guy Iverson (Water, Air, & Soil Pollution, 2015)

Statistical and perceptual updating: correlated impairments in right brain injury - Elisabeth Stöttinger; Alex Filipowicz; Elahe Marandi; Nadine Quehl; James Danckert; Britt Anderson (Experimental Brain Research, 2014)

Immigrants and refugees: the importance of dispersal in mediating biotic attrition under climate change - Alex S. Anderson; April E. Reside; Jeremy J. VanDerWal; Luke P. Shoo; Richard G. Pearson; Stephen E. Williams (Global Change Biology, 2012)
Montane tropical rainforests are critically important areas for global bird diversity, but are projected to be highly vulnerable to contemporary climate change. Upslope shifts of lowland species may partially offset declines in upland species but also result in a process of lowland biotic attrition. This latter process is contingent on the absence of species adapted to novel warm climates, and isolation from pools of potential colonizers. In the A ustralian Wet Tropics, species distribution modelling has forecast critical declines in suitable environmental area for upland endemic birds, raising the question of the future role of both natural and assisted dispersal in species survival, but information is lacking for important neighbouring rainforest regions. Here we use expanded geographic coverage of data to model the realized distributions of 120 bird species found in north‐eastern A ustralian rainforest, including species from potential source locations in the north and recipient locations in the south. We reaffirm previous conclusions as to the high vulnerability of this fauna to global warming, and extend the list of species whose suitable environmental area is projected to decrease. However, we find that expansion of suitable area for some species currently restricted to northern rainforests has the potential to offset biotic attrition in lowland forest of the A ustralian Wet Tropics. By examining contrasting dispersal scenarios, we show that responses to climate change in this region may critically depend on dispersal limitation, as climate change shifts the suitable environmental envelopes of many species south into currently unsuitable habitats. For lowland and northern species, future change in vegetation connectivity across contemporary habitat barriers is likely to be an important mediator of climate change impacts. In contrast, upland species are projected to become increasingly isolated and restricted. Their survival is likely to be more dependent on the viability of assisted migration, and the emergence and persistence of suitable environments at recipient locations.

Characterization of 12 microsatellite loci in the waterfall damselfly (Paraphlebia zoe) for use in population genetic applications - Christopher N. Anderson; Gregory F. Grether; Alex Cordoba-Aguilar (Conservation Genetics Resources, 2012)

Colorectal cancer screening behavior and health insurance status (United States) - B. Alex Matthews; Ruric C. Anderson; Ann B. Nattinger (Cancer Causes & Control, 2005)

Identification of potential inter-domain disulfides in three higher plant mitochondrial citrate synthases: Paradoxical differences in redox-sensitivity as compared with the animal enzyme - Fred J. Stevens; Alex Dong Li; S. Salman Lateef; Louise E. Anderson (Photosynthesis Research, 1997)

Reduced levels of cytochrome bf complex in transgenic tobacco leads to marked photochemical reduction of the plastoquinone pool, without significant change in acclimation to irradiance - Jan M. Anderson; G. Dean Price; Wah Soon Chow; Alex B. Hope; Murray R. Badger (Photosynthesis Research, 1997)

Chlamydomonas reinhardtii NADP-linked glyceraldehyde-3-phosphate dehydrogenase contains the cysteine residues identified as potentially domain-locking in the higher plant enzyme and is light activated - Alex Dong Li; Fred J. Stevens; Heather C. Huppe; Ralf Kersanach; Louise E. Anderson (Photosynthesis Research, 1997)